A new genus and species of ibis fly in the Lowermost Eocene amber of Oise (France) (Diptera: Athericidae) - Myskowiak, Justine; Nel, André (Zootaxa, 2014)
A new athericid genus and species, Eoatrichops jeanbernardi, gen. n., sp. n., is described, based on four specimens from the Lowermost Eocene of Oise (France). Its external morphology is analyzed and compared with of all genera of Athericidae. Eoatrichops is very similar to the modern genus Atrichops Verrall, differences concern the wing venation and tibial spur formula.